2007
DOI: 10.1021/ic700912q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Electrochemistry of Di- and Zerovalent Nickel, Palladium, and Platinum Monomers and Dimers Derived from an Enantiopure (S,S)-Tetra(tertiary Phosphine)

Abstract: The ligand (S,S)-1,1,4,7,10,10-hexaphenyl-1,4,7,10-tetraphosphadecane, (S,S)-tetraphos, reacts with hexa(aqua)nickel(II) chloride in the presence of trimethylsilyl triflate (TMSOTf) in dichloromethane to give the yellow square-planar complex [Ni{(R,R)-tetraphos}](OTf)2, which has been crystallographically characterized as the square-pyramidal, acetonitrile adduct [Ni(NCMe){(R,R)-tetraphos}]OTf. Cyclic voltammograms of the nickel(II) complex in dichloromethane and acetonitrile at 20 degrees C showed two reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…A plausible assignment for the decomposition pathway is dissociation of one or more phosphines from Ni 0 (P 4 N 2 ), followed by formation of multimetallic species in which the P 4 N 2 ligand bridges two or more nickel centers. In support of this assignment, Ni 0 (tetraphos) has been shown to isomerize to [Ni 0 2 (tetraphos) 2 ], in which the tetraphos ligands bridge both Ni centers …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A plausible assignment for the decomposition pathway is dissociation of one or more phosphines from Ni 0 (P 4 N 2 ), followed by formation of multimetallic species in which the P 4 N 2 ligand bridges two or more nickel centers. In support of this assignment, Ni 0 (tetraphos) has been shown to isomerize to [Ni 0 2 (tetraphos) 2 ], in which the tetraphos ligands bridge both Ni centers …”
Section: Resultsmentioning
confidence: 90%
“…Notably, 1 displays a square-pyramidal geometry in the solid state with an axial CH 3 CN ligand, with a τ 5 value of 0.02 . In contrast to 1 , the related complex [Ni­(tetraphos)­(CH 3 CN)] 2+ (tetraphos = ( R,R )-Ph 2 CH 2 CH 2 P­(Ph)­CH 2 CH 2 P­(Ph)­CH 2 CH 2 PPh 2 ) displays τ 5 values of 0.24 and 0.40 for two crystallographically independent molecules, indicating a moderately to strongly distorted square pyramidal geometry. This structural difference is a consequence of the cyclic P 2 N 2 fragment in the P 4 N 2 backbone, which possesses a small P–Ni–P angle of 80.23(2)°.…”
Section: Resultsmentioning
confidence: 99%
“…A number of parameters point to the potential for the differential force/rate response of reductive elimination for nickel compared to platinum. For example, nickel is smaller ( r = 1.24 Å) than platinum ( r = 1.36 Å), with concomitantly shorter M–P bonds (Δ d = 0.07 Å). Nickel­(II) complexes are also more prone to adopt a tetrahedral geometry and are more easily reduced than are Pt­(II) complexes. Importantly, energy decomposition analysis of ethylene dissociation from the group 10 bisphosphine complexes (PMe 3 ) 2 M­(π-H 2 CCH 2 ) (M = Ni, Pt) revealed that the preparation energy (Δ E prep ), which corresponds to the energy required to deform the two-coordinate (PMe 3 ) 2 M fragments from their equilibrium geometry to the geometry in the corresponding three-coordinate ethylene complexes, was significantly larger for platinum (Δ E prep = 30.2 kcal/mol) than for nickel (Δ E prep = 14.7 kcal/mol) . This suggests that the P–M–P bond angle of square-planar nickel complexes might be more pliable than the corresponding platinum complexes, leading to enhanced sensitivity to applied force.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction proceeds according to the equation: The occurrence of Ni(0) [8,9] or Ni(I) [10] in reaction (1) of ACS was postulated. Since the mechanism of catalytic action of the ACS enzyme is not fully understood [8,[11][12][13], models of methylation reactions involving nickel complexes and various methylation factors are being examined experimentally [9,[14][15][16][17][18][19]. Likewise, many complexes relevant to ACS enzyme are investigated experimentally [20][21][22][23][24] and computationally [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%